DIGITAL ADOPTION AND HOUSEHOLD RESILIENCE IN GHANA: THE ROLE OF HOUSEHOLD HEAD GENDER AND MARITAL - PHILIP KOFI SIKA EGYIR,CHRISTIANA MARTINA AFFUM AND JOHN AWOTWE ESHUN (My University, 2026)
Abstract This study examines the relationship between digital adoption and household resilience in Ghana, with particular attention to differences by household head gender and marital status. Using data from the FinScope Ghana 2022 Survey (FinMark Trust), the study investigates how internet awareness, internet use, digital device ownership or access, and selected digital financial usage influence household coping strategies and resilience. Ordinary Least Squares regression, interaction models, joint significance tests, and marginal effects estimation were employed. The findings reveal that digital adoption is positively and significantly associated with household resilience (coefficient = 0.050, p = 0.018), although the explanatory contribution is modest. The relationship does not differ significantly by household head gender (F = 0.80, p = 0.448) nor across marital status categories (F = 0.90, p = 0.466). The study contributes to development literature by providing empirical evidence on the relationship between digital adoption and household resilience in Ghana, offers practical guidance for policymakers and financial service providers on designing inclusive digital interventions, informs policy for addressing gender and marital-status disparities, and extends the Sustainable Livelihoods Framework to digital adoption contexts.